WTAP Accelerates Exhaustion of CD8+ T Cells and Progression of Hepatocellular Carcinoma by Promoting m6A Modification and Translation of PD1 mRNA - Rong Li; Shunle Li; Hua Li; Bingli Liu; Zimu Wang; Huanqin Lei; Yuting Li; Lijuan Jia; Junhui Li; Hongwei Lu; Meng Xu (Mediators of Inflammation)
The N6-methyladenosine (m6A) methylase WTAP has been identified as a proto-oncogene in multiple cancers, including hepatocellular carcinoma (HCC). Interestingly, although WTAP expression does not differ between normal liver and HCC tissues or across different stages of HCC, patients with higher WTAP expression exhibit significantly shorter median survival times (MSTs). Here, we found that WTAP was upregulated in tumor-infiltrating CD8+ T cells, which were more enriched in HCC patients compared to the controls. HCC patients also displayed higher PD1 levels and a greater proportion of exhausted CD8+ T cells (TCF+ PD1+). Moreover, WTAP promoted PD1 expression and suppressed the proliferation and immune activity of CD8+ T cells. In the co-culture system, WTAP-overexpressing CD8+ T cells enhanced the malignancy of HCC cells. Notably, WTAP silencing further augmented the boosting effect of PD1 silencing on CD8+ T cell immune activity and strengthened its inhibitory effect on HCC cell growth. As an m6A “writer”, WTAP increased the m6A level of PD1 mRNA, thereby promoting YTHDF1-mediated translation of PD1. Finally, in the HuNSG xenograft tumor model, WTAP knockdown not only alleviated CD8+ T cell exhaustion and inhibited tumor progression but also synergistically enhanced the antitumor efficacy of anti-PD1 therapy. In conclusion, WTAP promoted CD8+ T cell exhaustion and HCC progression by facilitating the m6A modification and translation of PD1 mRNA.